The Cardamom Law and Postcolonial Re-readings in Times of War - Marit Ursin; Ida Marie Lyså (Barn)
In this editorial, we explore the Cardamom Law through a postcolonial lens—scrutinising its convoluted origins, connotations and associations—to show how childhoods in the Nordic region are globally entangled.